Integrated pigweed management in soybean and grain sorghum - Hay, Marshall Mark (Kansas State University, 2019)
Palmer amaranth and waterhemp are among the most troublesome weeds in Kansas. The continued reliance on a single herbicide site of action has repeatedly resulted in the selection of herbicide resistant biotypes. It is likely that any anticipated future technologies will be met with the same fate as many other herbicides regarding Palmer amaranth and waterhemp if the technology is not implemented as part of an integrated system. An integrated system utilizes cultural, mechanical, and chemical control strategies to reduce the selection pressure on any one part of the system to delay the development of resistance. Field trials were implemented during 2017 and 2018 at three locations in dryland grain sorghum and soybean. The objective was to assess the control of Palmer amaranth or waterhemp with a winter wheat cover crop (CC), narrow row spacing (NRS), row-crop cultivation at 2.5 weeks after planting (WAP), and a comprehensive herbicide program to develop integrated-based management recommendations for dryland grain sorghum and soybean. Sixteen treatments were implemented in each crop to assess all possible combinations of three row spacings (76, 38, and 19-cm), CC, and row-crop cultivation. All treatments containing the herbicide program resulted in excellent Palmer amaranth or waterhemp control; therefore, these treatments were analyzed separately. Row-crop cultivation tended to offer greater than 50% reduction in density and biomass (3 and 8 WAP); whereas, mixed results were observed with CC. In about half of the site-years, CC resulted in 35 to 50% reduction in density and biomass (3 and 8 WAP), no differences were observed in one-fourth of the site-years, and approximately a 50% increase in density was observed in the remainder. The only direct benefit offered from NRS (< 76 cm) was a reduction (about 30%) in 8 WAP biomass. In conclusion, RC reduced the selection pressure placed on pigweed during POST herbicide applications through reductions in density and biomass 3 WAP; whereas RC, CC, and NRS reduced late season biomass which could reduce yield losses and subsequently weed seed production.
Keywords: Pigweed; herbicide resistance; integrated strategies; cultivation; cover crop; narrow row widths